Dual Clinical Practice (DCP) policy to improve the retention of human resources for health in Rwanda: a mid-term review using a cross-sectional and retrospective study design - Kizito Kayumba; Corneille Ntihabose; Sabine Musange Furere; Bernard Ngabo; Piero Irakiza; Felix K. Rubuga; Nathalie Umutoni; Ina Rukundo Kalisa; Pascal Birindabagabo; Emile Rwamasirabo; Emmanuel Kayibanda; Patience Mukundirukuri; et al. (BMC Health Services Research)
Abstract Background Despite the high demand for public services globally, ensuring the quality of services provided by public health facilities is challenging. Poor remuneration of public sector health care providers (HCPs) drives their migration to private health facilities. The Dual Clinical Practice (DCP) Policy in Rwanda represents a strategic initiative aimed at retaining healthcare professionals in public health facilities, allowing them to engage in private practice concurrently. This study assesses the implementation challenges and identifies opportunities for potential reformulation of DCP schemes. Methods This study employed a mixed methods approach, incorporating both cross-sectional and retrospective designs across six Rwandan public hospitals. Quantitative and qualitative data were collected through key informant interviews (KIIs) and joint interviews (JIs), as well as through the analysis of health facility records obtained from the Health Management Information System (HMIS) and the Electronic Medical Record (EMR). Qualitative data were analyzed using Atlas.ti software, while quantitative data were analyzed using Microsoft Excel. Results The study involved participants from six Rwandan hospitals, including 20 healthcare providers and 32 patients. Qualitative results revealed that a substantial majority of health care providers supported the DCP policy, with a high patient satisfaction rate of 81% regarding DCP services. However, challenges emerged, including limited awareness of the policy and difficulties in tracking DCP engagements. Quantitative data from the HMIS and EMR indicated an increase in patient enrollment across most facilities, with DCP outpatient visits accounting for a significant percentage of total visits in some hospitals. While the DCP contributed positively to hospital revenues, concerns about the sustainability of the scheme and the adequacy of health care remuneration were highlighted, calling for a review of DCP policy involving stakeholders beyond the Ministry of Health. Conclusion This study found that the DCP policy in Rwanda positively impacted healthcare provider retention, patient satisfaction, and hospital revenues. Providers expressed strong support for the policy, and patient satisfaction was high, with 81% of patients reporting positive experiences with DCP services. The scheme contributed to increased patient enrollment and hospital revenue, particularly in urban facilities. However, challenges, such as limited awareness of the policy among healthcare providers and difficulties in tracking DCP engagements, were noted. Additionally, concerns about the sustainability of the DCP and the adequacy of healthcare remuneration highlighted the need for policy revisions. To address these challenges, a collaborative approach involving stakeholders such as tax authorities, hospital administrations, and health insurance companies is necessary. Additionally, our study highlights the critical role of investments in physical infrastructure to support the long-term success of DCP. Enhancing infrastructure would not only ensure better healthcare quality but also support the retention of providers in both urban and rural settings.